2014
DOI: 10.1108/ilt-01-2012-0008
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze film characteristics of conical bearings operating with non-Newtonian lubricants – Rabinowitsch fluid model

Abstract: Purpose -The purpose of this paper is to present a theoretical study of non-Newtonian effects in conical squeeze-film plates that is based on the Rabinowitsch fluid model. Design/methodology/approach -A non-linear, modified Reynolds equation accounting for the non-Newtonian properties following the cubic stress law equation is derived. Through a small perturbation method, first-order closed-form solutions are obtained. Findings -It is found that the non-Newtonian properties of dilatant fluids increase the load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 16 publications
7
16
0
Order By: Relevance
“…Variation of the load-carrying capacity L* with film height h* for different values of ω and θ with Hp=0.1,Rp=0.1, and Q=0.25 is presented in Figure 7. It is found that the load capacity L* decreases for increasing values of film thickness h*. Further, the dimensionless load capacity L* decreases with increasing values of θ with ω and agrees very well with the results of Hsu et al., 6 which has been shown in Figure 7.
Figure 6.Variation of the load-carrying capacity L* with film height h* for different ω, H p , and R p with
…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Variation of the load-carrying capacity L* with film height h* for different values of ω and θ with Hp=0.1,Rp=0.1, and Q=0.25 is presented in Figure 7. It is found that the load capacity L* decreases for increasing values of film thickness h*. Further, the dimensionless load capacity L* decreases with increasing values of θ with ω and agrees very well with the results of Hsu et al., 6 which has been shown in Figure 7.
Figure 6.Variation of the load-carrying capacity L* with film height h* for different ω, H p , and R p with
…”
Section: Resultssupporting
confidence: 89%
“…Increasing the viscosity variation decreases the film pressure and it agrees with the study of Siddangouda et al. 6
Figure 2.Variation of the dimensionless film pressure P* with x* for different values of ω and Q with h*=0.3, Hp=0.1,Rp=0.1, and θ = 45°.
…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is hopeful to provide comparisons and numerical tables for dimensionless load-carrying capacity with different half cone angle. The simulated data from Table 1 to 4 are compared with Hsu et al 9 for the non-porous case. Tables 1 and 2…”
Section: Resultsmentioning
confidence: 99%
“…This non-Newtonian Rabinowitsch fluid model is applicable to dilatant lubricants for 0 n < , to Newtonian lubricants for 0 n = , and to pseudo-plastic lubricants for 0 n > . Many studies have applied this model to investigate the thin film lubrication systems, for example, the squeeze film bearings by Lin [8] and Hsu et al [9], the hydrostatic bearings by Sharma et al [10], the journal bearings by Bourging and Gay [11], and the inclined plane slider bearings by Lin [12]. According to their results, the influences of non-Newtonian Rabinowitsch fluids on the lubrication performances of the squeeze film bearings, the hydrostatic bearings, the journal bearings and the inclined plane slider bearings are significantly apparent.…”
Section: Introductionmentioning
confidence: 99%